Application of advanced technologies in shade matching: A spectrophotometer - Anđelković Aleksandra; Marković Dubravka; Petronijević Branislava; Jeremić-Knežević Milica; Veselinović Valentina; Predin Tanja (Serbian Medical Society - Dental Section, Belgrade, 2010)
One of many challenges in cosmetic dentistry is to accomplish appropriate and satisfactory reproduction of natural shade of teeth and in that way to make successful restoration. The procedure of choosing a shade can be performed using visual method or by an instrument. The kind of shade guide, individual ability to choose shades and conditions the choice is made under, all have influence on reliability and accuracy of the procedure. Therefore, it is necessary to introduce instrumental color determination in everyday work. The instrumental color determination method considers use of a spectrophotometer, a colorimeter and a digital camera or even the combination of all three in shade matching. The purpose of this article was to present all amenities and advantages of the instrumental color determination in shade matching through the demonstration of the clinical performances of an intraoral spectrophotometer VITA Easyshade Compact device. VITA Easyshade Compact device provides fast and reliable measuring and gives results that are not influenced by the conditions under which the shade was chosen or by the person who made choice. Shade matching using a spectrophotometer meets all the requirements for choosing the shade by vision, therefore it is recommended for clinical work.